Politik Hukum Hak Pengelolaan Atas Tanah Ulayat dalam Rangka Perlindungan dan Pemanfaatan Hak Masyarakat Hukum Adat: Studi : Suku Baduy di Kabupaten Lebak (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The management rights over ulayat land represent a vital resource for human life and community welfare. This study examines constitutional rights to land and natural resources, as well as the role of the state in land management and relevant regulations, with a specific focus on the Baduy indigenous community in Lebak Regency. The objective is to analyze the effectiveness of existing regulations in protecting and facilitating the rights of the Baduy people. Utilizing a socio-legal research approach, along with statutory and conceptual frameworks, data were collected through literature reviews and interviews. The findings highlight the need for a clear and comprehensive legal framework from the government regarding land management, as well as recognition and protection of indigenous land rights. The study recommends agrarian reform to address land inequality and ensure fair and sustainable use and distribution of land resources.